Binding of pDNA with cDNA using hybridization strategy towards monitoring of Haemophilus influenza genome in human plasma samples - Saadati, Arezoo; Hassanpour, Soodabeh; Hasanzadeh, Mohammad; Shadjou, Nasrin (International journal of biological macromolecules, 2020)
Haemophilus Influenza leads to respiratory infections such as sinusitis, acute otitis media, pneumonia and bronchitis. In addition, it causes invasive infections such as cellulite, septic arthritis, and meningitis. Therefore, quick and sensitive detection of H. influenza is of great importance in medical microbiology. In this study, a novel DNA-based bioassay was developed to the monitoring of Haemophilus influenza genome in human plasma samples using binding of pDNA with cDNA. DNA hybridization strategy was used to investigation of DNAs binding. For this purpose, silver nanoparticle doped graphene quantum dots inks functionalized by D-penicillamine (Ag NPs-DPA-GQDs) were synthesized and deposited on the surface of glass carbon electrode (GCE). Also, gold nanoparticles functionalized with cysteamine (CysA-AuNPs) were deposited on the surface of the Ag-DPA-GQDs modified GCE. Afterward, thiolated DNA probe was immobilized on the surface of the modified electrode. DNA hybridization was monitored using square wave voltammetry (SWV) technique. Engineered genosensor indicated good performance with high specificity and sensitivity for detection of Haemophilus influenza genome. Under optimal conditions, linear range and low limit of quantitation (LLOQ) were obtained as target concentrations ranging from 1 pM-1 ZM and 1 ZM, respectively. The designed biosensor also showed high capability of discriminating one-base, two-base and three-base mismatched sequences. Also, the prepared genosensor could be easily regenerated and reused to evaluate hybridization process.
Keywords: Electrochemical Techniques; Cell-Free Nucleic Acids; kovové nanočástice; DNA hybridization; Haemophilus influenzae; Reproducibility of Results; lidé; hybridizace nukleových kyselin; Haemophilus influenza; volné cirkulující nukleové kyseliny; Metal Nanoparticles; Bioassay; Genome, Bacterial; komplementární DNA; Biosensing Techniques; genom bakteriální; reprodukovatelnost výsledků; Silver nanoparticles; elektrochemické techniky; biosenzitivní techniky; Nucleic Acid Hybridization; Quantum Dots; kvantové tečky; DNA, Complementary; Nucleic acid binding; Humans